Intensive patients’ care program ameliorates anxiety and depression, and sustained anxiety correlates with worse overall survival in renal cell carcinoma patients underwent radical nephrectomy - Song, Bingbing; Zhang, Yuling; Wang, Yanjie; An, Xushu (Translational Cancer Research, 2018)
Background: This study aimed to investigate the effect of an intensive patients’ care program (IPCP) on anxiety, depression, and survival rate of renal cell carcinoma (RCC) patients post radical nephrectomy. Methods: This study consisted of two stages: a randomized, controlled stage (stage I) and a long-term follow-up stage (stage II). A total of 182 RCC patients who underwent radical nephrectomy were consecutively recruited and were allotted into a IPCP group (IPCP plus usual care), or a control group (only usual care) in a 1:1 ratio. Anxiety and depression were evaluated by HADS and SAS/SDS at baseline (M0), M3, M6, M9 and M12. Overall survival (OS) was documented. Results: The decrease of HADS-A score was larger, the percentage of patients with anxiety at M12 assessed by HADS-A score was reduced and the percentage of patients with light anxiety at M12 assessed by HADS-A score was greater in IPCP group compared with control group. The SAS score at M3, M6, M9 and M12 were declined and the SAS score reduction at M12 was greater in IPCP group compared with control group. The reduction of HADS-D score in IPCP group was greater compared with control group. The SDS score at M12 was reduced in IPCP group compared with control group, and the decrease of SDS score at M12 in IPCP group was larger compared with control group. Patients with sustained anxiety assessed by HADS-A score and SAS score had worse OS compared with patients without sustained anxiety. Conclusions: IPCP ameliorated anxiety and depression, and sustained anxiety correlated with worse OS in RCC patients post radical nephrectomy.